PENGARUH METALLIC CATALYTIC CONVERTER TEMBAGA BERLAPIS CHROME DALAM MENURUNKAN EMISI GAS BUANG MESIN SEPEDA MOTOR EMPAT LANGKAH - Sudirman Rizki Ariyanto; Retno Wulandari; Suprayitno Suprayitno; Pramuko Ilmu Purboputro (Media Mesin: Majalah Teknik Mesin, 2022)
Transition metals have emerged and have begun to be widely researched as alternative materials in the manufacture of metallic catalytic converters (MCC). The selection of transition metals is based on the availability of abundant materials in the market, besides that the price of transition metals tends to be cheaper when compared to PGM. Therefore, through this study, an analysis of the effect of chrome-plated copper MCC (CuCr) was carried out on CO and HC exhaust emissions. Emission testing is carried out under two conditions. The first condition is the condition where the test vehicle still uses a standard exhaust, while in the second condition the test vehicle uses a modified exhaust equipped with MCC CuCr technology. The test vehicle used was the 2005 Honda Supra Fit. The emission testing process was carried out based on the SNI 09-71118.1-2005 standard which was then compared with the Regulation of the Minister of the Environment, Number 05 of 2006. The research findings show that MCC CuCr is proven to be able to reduce exhaust emissions by an average reduction of 24% for CO emissions and 30% for HC emissions. The emission test results show that the measured CO emission is 1.68% Vol while the CO emission threshold is 5.5% Vol. Meanwhile, the measured HC emission is 1719 ppmVol while the HC emission threshold is 2400 ppmVol. Therefore, it can be concluded that MCC CuCr passed the emission test in accordance with the Regulation of the State Minister of the Environment number 5 of 2006.